Fostering Student Discipline through School Culture at MI Miftahul Ulum Tulung Jaya - Binti Khoiriyah; Misrodin; Siti Nur Karismawati (CV. Edujavare Publishing, 2026)
This study aims to describe the forms of school culture implemented to foster student discipline, the process of cultivating this discipline through school culture, and the roles of the madrasa principal, teachers, students, educational staff, and parents in this endeavor at MI Miftahul Ulum Tulung Jaya. A qualitative approach utilizing a case study design was employed. The research was conducted at MI Miftahul Ulum Tulung Jaya during the current semester of the 2025/2026 academic year. Informants—comprising the madrasa principal, teachers, students, and parents—were selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation. Qualitative data analysis was performed through processes of organization, reduction, presentation, and conclusion drawing. The results indicate that the school culture implemented to foster discipline includes punctuality, adherence to regulations, the habituation of religious activities, maintaining environmental cleanliness, modeling by teachers and the principal, and fostering responsibility through classroom duty rosters. The process of cultivating discipline involves the dissemination of rules, habituation, role modeling, supervision and guidance, and continuous evaluation. The madrasa principal acts as a leader, director, supervisor, and evaluator; teachers serve as role models, guides, motivators, and mentors; students act as implementers of the discipline culture; and parents play a role in reinforcing disciplined habits within the family environment. The findings demonstrate that consistent implementation of school culture and synergy among all members of the madrasa community are crucial factors in shaping student discipline.